2023
DOI: 10.3390/polym15112504
|View full text |Cite
|
Sign up to set email alerts
|

Durability of Polymer-Modified Asphalt Mixture with Wasted Tire Powder and Epoxy Resin under Tropical Climate Curing Conditions

Abstract: The quality of pavements in tropical climates is negatively affected by the frequent wet and dry cycles during the rainy season, as well as by issues related to overloading from heavy trucks and traffic congestion. Contributing to this deterioration are factors such as acid rainwater, heavy traffic oils, and municipal debris. In light of these challenges, this study aims to assess the viability of a polymer-modified asphalt concrete mixture. This study investigates the feasibility of a polymer-modified asphalt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…The asphalt binder and epoxy resins were obtained from the Korean SK petroleum company, known for their high-quality products. The magnesium additive was sourced from a reliable Korea Import Company in Seoul, South Korea [ 18 , 19 ]. The aggregate used in this study was obtained from a local asphalt plant, ensuring proximity and adherence to regional specifications.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The asphalt binder and epoxy resins were obtained from the Korean SK petroleum company, known for their high-quality products. The magnesium additive was sourced from a reliable Korea Import Company in Seoul, South Korea [ 18 , 19 ]. The aggregate used in this study was obtained from a local asphalt plant, ensuring proximity and adherence to regional specifications.…”
Section: Methodsmentioning
confidence: 99%
“…The WPCM was then incorporated into the mixture, and the mixing process continued for about 1–2 min to facilitate thorough blending. Throughout the entire process, strict control of temperature and duration ensured optimal bonding and homogeneity [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, whether from the perspective of waste disposal or simply to improve the performance of bitumen, many scholars have undertaken work on the modification of bitumen using waste rubber powder [9,10]. It was found that waste rubber powder has many advantages as an asphalt modifier, such as improving the durability, fatigue resistance, and economic benefits of asphalt pavement [11][12][13]. Li et al pointed out that the aging resistance of waste-tire-rubber-powder-modified asphalt is also excellent [14].…”
Section: Of 13mentioning
confidence: 99%
“…Recently, epoxy resin and crumb rubber powder (CRP) have gained significant attention as valuable additives in asphalt mixtures due to their unique properties and potential benefits [14][15][16]. Epoxy resin, known for its adhesive and cohesive characteristics, has been employed to enhance the bonding between asphalt and aggregate particles, resulting in improved asphalt mix durability [17][18][19].…”
Section: Introductionmentioning
confidence: 99%